A development of supply chain management (SCM) practices and competitive advantages in manufacturing industries [electronic resource] - Chu, Hui Ping, 1990-, author (2014)
Project Paper (Sarjana Muda Pengurusan (Teknologi)) - Universiti Teknologi Malaysia, 2014